Identificación y determinación probabilística de los grupos pobres en la zona rural de Risaralda. (2021)
In this paper is developed an instrument of likelihood identification of the vulnerable groups (poor groups) of “Risaralda´s countryside population” and it gives empiric evidence that helps to clarify its socioeconomic profiles; that’s why it is used a model of logistical discrimination and is defined the phenomenon of the poverty, starting from the focus of capacities and rights. Among the variables with more capacity to discriminate the poverty stand out: the level of studies of the home’s head, and the rest of its participants, the number of working people inside the home, the percentage of younger people at home, the home’s head age and the variable gender in the head of the home. This last, topic it’s equal to a verification of the hypothesis of “femalehood of the poverty” in the study area, it marks the difference whit other results of similar studies in Colombia.